Математична та структурна моделі інформаційних технологій удосконалення процесу сушіння поліграфічних матеріалів - Коляно, Ярослав Юрійович; Сасс, Тарас Стефанович; Іваник, Євген Григорович; Сікора, Оксана Володимирівна; Дорошенко, Микола Васильович (Kamianets-Podilskyi National Ivan Ohiienko University, 2016)
The structural model of information technology drying of printing materials, based on mathematical modeling processes teplomasoperenesennya in capillary-porous colloidal bodies. The results of analysis of non-stationary solution to the problem termovolohoprovidnosti plate printing systems suitable for optimization of drying and used in addressing energy efficiency and ensure the required quality printed materials (cardboard, paper, polyurethane).